Intercultural missional leadership : a narrative approach focusing on "Tabeh village" missional work in Cambodia - Niemandt, Cornelius Johannes Petrus (Nelus) (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2016.